Solar radiation visibility testing algorithm for precise shadow distribution for spatial steel structural thermal analysis under sunlight - Zhang, Kai; Yu, Liyang; Chen, Deshen; Qian, Hongliang (Case studies in thermal engineering, 2024)
As a large-span spatial steel structure, the radio telescope, characterized by its extensive span and numerous structural components, is sensitive to temperature gradients and susceptible to localized deformations induced by non-uniform temperature filed under sunlight, thereby affecting the operational performance. In order to calculate the shadow distribution of the structure, this study proposes a solar radiation visibility testing algorithm based on the depth buffer. To validate the accuracy of the proposed algorithm, the shadow distribution of a shading device is calculated employing the new algorithm, theoretical methods, and Ladybug tools. The results show that the shadow distribution obtained by the three methods is consistent. The thermal numerical simulation of the grid structure using the direct solar radiation calculated by the proposed algorithm is compared with the experiment results, and the error is below 5 %. Taking a radio telescope as an engineering application, the temperature distribution and pointing accuracy under solar are calculated. 9:00 and 16:00 have the worst pointing accuracy, while 11:00–13:00 has the best pointing accuracy. This study can provide a reference for the calculation of temperature field of spatial steel structure which is sensitive to sunlight temperature.